2018
DOI: 10.1016/j.redox.2017.11.007
|View full text |Cite
|
Sign up to set email alerts
|

Resveratrol attenuates testicular apoptosis in type 1 diabetic mice: Role of Akt-mediated Nrf2 activation and p62-dependent Keap1 degradation

Abstract: Infertility is a common complication in diabetic men, mainly due to the loss of germ cells by apoptotic cell death. However, effective and safe approaches to prevent diabetic induction of testicular apoptosis for diabetic patients have not been available. Resveratrol (RSV), a group of compounds called polyphenols from plants, has been indicated its promising used clinically for cancers and cardiovascular diseases. Therefore, the present study aimed determining whether RSV attenuates type 1 diabetes (T1D)-induc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
68
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 126 publications
(76 citation statements)
references
References 49 publications
(67 reference statements)
8
68
0
Order By: Relevance
“…The mechanism of Nrf2 regulation has been widely studied [42,43]. Several recent studies have suggested that the activition of Nrf2 was regulated by Akt/GSK-3β/Fyn mediated degradation and nuclear export of Nrf2 [22,44]. In this study, we detected signi cantly decreased activation of the Akt/GSK-3β/Fyn pathway in senescent CD4 + T cells.…”
Section: Discussionsupporting
confidence: 53%
“…The mechanism of Nrf2 regulation has been widely studied [42,43]. Several recent studies have suggested that the activition of Nrf2 was regulated by Akt/GSK-3β/Fyn mediated degradation and nuclear export of Nrf2 [22,44]. In this study, we detected signi cantly decreased activation of the Akt/GSK-3β/Fyn pathway in senescent CD4 + T cells.…”
Section: Discussionsupporting
confidence: 53%
“…The decreased transcriptional activity of Nrf2 due to hyperglycaemia caused weakened antioxidant defence system and may represent an essential pathological mechanism in diabetic male infertility. Targeting and inducing Nrf2 have become a potential therapeutic strategy in diabetic male infertility (Ma et al, ; Wang et al, ; Zhao et al, ). In our research, we found that DZ could reduce the accumulation of ROS and enhance the expression of antioxidant enzymes in the testis tissue of mice by activating Nrf2.…”
Section: Discussionmentioning
confidence: 99%
“…[32] Moreover, Zhao et al determined that RSV attenuated type 1 diabetes (T1D)-induced apoptosis in testicular apoptotic cells, which was mainly associated with Akt-mediated Nrf2 activation via p62-dependent Keap1 degradation. [33] Current clinical trials have shown resveratrol was well tolerated and beneficial biomarkers for neurological diseases, cardiovascular diseases and diabetes. [71] However, it has a fuzzy or even detrimental effect on certain types of cancer and NAFLD (Nonalcoholic fatty liver disease).…”
Section: Resveratrol and Its Analogsmentioning
confidence: 99%